Cholinesterase Inhibitory Triterpenes from Perovskia atriplicifolia - Perveen, S.; AL-Taweel, A.M.; Fawzy, G.A.; Ibrahim, T.A.; Malik, A.; Khan, A. (Asian Journal of Chemistry, 2014)
Nine compounds including b-amyrin (1), erythrodiol (2), oleanolic acid (3), 3b-hydroxy-11,13(18)-oleanadien-28-oic acid (4), glycyrrhetinic acid (5), 2a,3b-dihydroxyolean-12-en-28-methyl ester (6), 2a,3b-dihydroxyolean-12-en-28-oic acid (7), 2a,3b,24-trihydroxyolean-12-en-28-oic acid (8) and 2a,3b,19b-trihydroxyurs-12-en-28-oic acid (9), have been isolated from Perovskia atriplicifolia. Their structures have been established with the help of different spectral data. All of these compounds were tested for cholinesterase inhibitory activity. Among the tested compounds, 8 and 9 were found to be the most active against both enzymes, with a significant butyrylcholinesterase (BChE) inhibitory activity demonstrating IC50 values 9.50 and 13.52 mM, respectively, compared to galanthamine standard (IC50: 8.51 mM).